2012
DOI: 10.1603/en12042
|View full text |Cite
|
Sign up to set email alerts
|

Ants Contribute Significantly to the Pollination of a Biodiesel Plant,Jatropha curcas

Abstract: Ants are the most abundant visitors to the flowers of Jatropha curcas L., but it is not clear how much they contribute to the pollination of this plant. In this study, we observed floral visitor assemblage and foraging behavior of ants, measured pollen loads carried by ants and deposited on stigmas, and determined the contribution of ants to the female reproductive success of J. curcas through exclusion experiments. Ants were the most abundant pollinators, accounting for 71.03 and 78.17% of total visits at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Our previous study found that fire ants frequently foraged B. napus flowers, possibly producing negative effects on flower-visiting insects, including the Chinese honey bee Apis cerana F. (Hymenoptera: Apidae) and the cabbage white butterfly Pieris rapae (L.) (Lepidoptera: Pieridae). These flower-visiting insects usually play an important role in the reproduction of plants (Hickman 1974;Gómez et al 1996;Raju & Ezradanam 2002;de Vega et al 2009;Luo et al 2011Luo et al , 2012. Furthermore, fire ant workers foraged more frequently on plants when aphids were present, potentially leading to an increased problem for the pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that fire ants frequently foraged B. napus flowers, possibly producing negative effects on flower-visiting insects, including the Chinese honey bee Apis cerana F. (Hymenoptera: Apidae) and the cabbage white butterfly Pieris rapae (L.) (Lepidoptera: Pieridae). These flower-visiting insects usually play an important role in the reproduction of plants (Hickman 1974;Gómez et al 1996;Raju & Ezradanam 2002;de Vega et al 2009;Luo et al 2011Luo et al , 2012. Furthermore, fire ant workers foraged more frequently on plants when aphids were present, potentially leading to an increased problem for the pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Ants also use cantharidin as a feeding deterrent in some species (Carrel & Eisner 1974), and they are an important pollinator in several plant species (Beattie 2006;de Vega et al 2014). In the three ant genera recorded in this study, Nylanderia are known as pollinators of the plants Petrosavia sakuraii (Petrosaviaceae) (Takahashi et al 1993), Balanophora tobiracola (Balanophoraceae) (Kawakita & Kato 2002) and Jatropha curcas (Euphorbiaceae) (Luo et al 2012). Monomorium are known as pollinators of the orchid Microtis parviflora (Orchidaceae) (Peakall & Beattie 1989) and Pristomyrmex are visitors to extrafloral nectaries of the plant Bletilla striata (Orchidaceae) (Sugiura 1995) and Terminalia catappa (Combretaceae) (Sugiura 2010).…”
Section: Discussionmentioning
confidence: 83%
“…), Balanophora tobiracola (Balanophoraceae) (Kawakita & Kato ) and Jatropha curcas (Euphorbiaceae) (Luo et al. ). Monomorium are known as pollinators of the orchid Microtis parviflora (Orchidaceae) (Peakall & Beattie ) and Pristomyrmex are visitors to extrafloral nectaries of the plant Bletilla striata (Orchidaceae) (Sugiura ) and Terminalia catappa (Combretaceae) (Sugiura ).…”
Section: Discussionmentioning
confidence: 99%
“…This ant also pollinates Mediterranean shrubs Retama sphaerocarpa, Frankenia thymifolia ( Gomez et al. 1996 ), Jatropha curcas ( Luo et al. 2012 ), and plants in the family Euphorbiaceae ( Reddi and Reddi 1984 , Schurch et al.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of bristle on its smooth integument makes it unsuitable to carry mango pollen ( Corlett 2004 ). However, Iridomyrmex anceps was reported by Luo et al. (2012) to be a pollinator of J .…”
Section: Discussionmentioning
confidence: 99%